Conjugational Transformation of Wild Type Bacillus halodurans CM1 by Methylated Recombinant Plasmid Harbouring a Gene Encoding for Alkaline Protease and the Protease Activity Assay of the Transformant - Valerry Athalia Priyanka; Maria Ulfah; Lina Mulyawati; Abinawanto; is helianti (HAYATI Journal of Biosciences, 2022)
Protease contributes significantly to various industrial sectors, as shown by its increasing demand. An indigenous previously isolated bacteria, Bacillus halodurans CM1, is a wild-type bacterium whose ability to produce alkalotermophilic protease. In this study, the transformation of methylated pBBRE194 plasmid containing alkaline protease gene from this strain (PBBRE194-prot-CM1) into itself using a conjugation approach was conducted, and the measurement of the alkaline protease activity of the recombinant bacterium was carried out. The recombinant B. halodurans CM1 has been verified to carry the methylated pBBRE194 prot-CM1 by examining its ability to degrade protein in media containing skim milk and tetracycline, but also by amplifying tetracycline resistance gene sequence with 1,024 bp length of plasmid pBBRE194 prot-CM1 by PCR method from the recombinant bacterium. The results confirmed that recombinant B. halodurans CM1 was positively harboring plasmid pBBRE194 prot-CM1. Alkaline protease produced by recombinant CM1 reached higher activity than wild type between 18-36 h of cultivation. The alkalotermophilic wild type B. halodurans could accept the recombinant plasmid into their cells via conjugational transformation is firstly reported to our further knowledge.